RATIO DECIDENDI DALAM PUTUSAN REHABILITASI MEDIS TERHADAP PELAKU PENYALAHGUNAAN NARKOTIKA BAGI DIRI SENDIRI - Gilang Rahadian Saputra; Ismawati Septiningsih (Verstek, 2021)
This article aims to analyze the judge's considerations in passing a decision on rehabilitation for perpetrators of Narcotics Abuse for Self Group I not plants, as well as the legal instruments that regulate it. This type of legal research is normative legal research. Based on the research it was found that to determine whether abusers can be rehabilitated or not is based on the characteristics and conditions of the perpetrators, in addition to determining the classification of abusers who can be rehabilitated judges need to pay attention to the Circular of the Supreme Court (SEMA) Number 4 of 2010 concerning Placement of Abuse, Victims of Abuse and Narcotics addicts into Medical and Social Rehabilitation Institutions.Keywords: Narcotics Abuser; Medical Rehabilitation; Social Rehabilitation